Analysis of the Role of Communication to Improve the Productivity and Efficiency of Employee Performance at the Mojokerto City Education and Culture Office - Firmansyah, Oktavia Maharani Yuli; Hariyono, Catrina Agustin; Novitaningrum, Rifda Lutfi; Buono, Yuliantoro Wahyu Tirto; Wulandari, Ruri Nurul Aeni; Puspasari, Durinta (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
This research is motivated by the importance of communication as a basis in the world of work, which plays a vital role in achieving individual and organizational goals. The inability to communicate effectively can hinder organizational performance, causing coordination difficulties, misunderstandings between colleagues, and decreased productivity. This research uses a descriptive method with a qualitative approach. The primary and secondary data used were obtained through purposive sampling. Observation and interview techniques were used to collect data, while data analysis was conducted using the Miles and Huberman model. The results and discussion here convey that by using the SPAN LAPOR application and the results of interviews with employees armed with this application, communication can run effectively between reporters and officials, making communication easier.